2004
DOI: 10.1542/peds.113.5.e418
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Relationship Between the Onset of Type 1 Diabetes and Celiac Disease: A Study Based on Immunoglobulin A Antitransglutaminase Screening

Abstract: ABSTRACT. Objective. The association of celiac disease (CD) and type 1 diabetes is now clearly documented. Immunoglobulin A (IgA) antitransglutaminase antibodies were measured to determine the prevalence of celiac disease in a diabetic population of children and to determine the temporal relationship between type 1 diabetes onset and CD.Methods. We measured IgA antitransglutaminase antibodies using human recombinant antigen in parallel with classical markers (IgA and IgG antigliadin, IgA antiendomysium) in 284… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
1
28
0
4
Order By: Relevance
“…Linfoma de Hodgkin e adenocarcinoma intestinal são mais comuns entre os celíacos do que na população geral (6), e o risco destas complicações parece ser proporcional ao tempo de exposição ao glúten (10). Como há fortes evidências de que a dieta isenta de glúten reverte ou pelo menos diminui o risco destas complicações, é recomendado o diagnóstico precoce com a pronta instituição da dieta sem glúten em todos os pacientes diabéticos tipo 1 com doença celíaca, mesmo que assintomática, a fi m de prevenir o desenvolvimento destas e outras complicações (9).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Linfoma de Hodgkin e adenocarcinoma intestinal são mais comuns entre os celíacos do que na população geral (6), e o risco destas complicações parece ser proporcional ao tempo de exposição ao glúten (10). Como há fortes evidências de que a dieta isenta de glúten reverte ou pelo menos diminui o risco destas complicações, é recomendado o diagnóstico precoce com a pronta instituição da dieta sem glúten em todos os pacientes diabéticos tipo 1 com doença celíaca, mesmo que assintomática, a fi m de prevenir o desenvolvimento destas e outras complicações (9).…”
Section: Discussionunclassified
“…O anticorpo antitransglutaminase tecidual humana IgA tem sido recomendado como o de escolha (10) por apresentar sensibilidade superior ao antiendomísio IgA, não obstante a especifi cidade semelhante. Para evitar o encontro de falso-negativos para estes anticorpos, é recomendada a verifi cação dos níveis séricos de IgA durante o rastreamento (10,13). Aqueles pacientes que apresentam sorologia positiva devem ser submetidos à endoscopia digestiva alta com biópsia de intestino delgado para a confi rmação da doença.…”
Section: Discussionunclassified
“…Patients with type 1 diabetes and positive celiac disease related antibodies can be identified at onset of diabetes (54). This implies that the two diseases may have developed concurrently or at least in a similar time frame.…”
Section: Associated Conditions (Table 1)mentioning
confidence: 99%
“…It has been reported that serological screening for CD at the onset of T1DM allows the identification of 1% of CD patients and that this prevalence rises to at least 5% in the following 5 years [28]. Moreover, according to other published data, antibody positivity for CD may appear within 10 years from the initial diagnosis of T1DM and, in the 90% of cases, within the first 2 years from the diagnosis [18,25,[45][46][47][48]. Therefore, if CD-serological tests are negative at the onset of T1DM, patients should be reassessed for these antibodies annually for the first 4 years and once every 2 years for the following 6 years [47,49].…”
Section: Serological Screening For CD In T1dmmentioning
confidence: 99%